Respuesta :
Answer:
Step-by-step explanation:Simplifying
2a + 6b = 100
Solving
2a + 6b = 100
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-6b' to each side of the equation.
2a + 6b + -6b = 100 + -6b
Combine like terms: 6b + -6b = 0
2a + 0 = 100 + -6b
2a = 100 + -6b
Divide each side by '2'.
a = 50 + -3b
Simplifying
a = 50 + -3b
Answer:
5(50x - 3bx + 50 - a) or 5(a + 3b) (Depending on the question and what is asked)
Step-by-step explanation:
2a + 6b = 100
a = 50-3b
b = 50/3 - 1/3a
replace
5a + 15b =
5*50-3b + 15*50/3 - 1/3a =
5(50x - 3bx + 50 - a)
^This would be the answer if we use the same value of a and b from the 2a+6b=100 equation.
If we use a unknown value for a and b. Then, the answer would be 5(a + 3b).